2008
DOI: 10.1007/s00227-008-1052-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting zooplankton response to environmental changes in a temperate estuarine ecosystem

Abstract: A novel strategy that allows to predict the responses of zooplanktonic species to environmental conditions in an estuarine temperate ecosystem (Mondego estuary) is presented. It uses 12 indicator species from the zooplanktonic Mondego database (102 species) that are common members of the different habitats, characterized by their specific hydrological conditions. Indicator-species analysis (ISA) was used to define and describe which species were typical of each of the five sampling stations in a 4-year study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…Salinity stands out as one of the most important parameters in environments with strong zonation patterns (Gaudy et al, 1995;Marques et al, 2008), or in cases where man-made changes have altered the freshwater inputs in the ecosystem (Sei et al, 1996;Badosa et al, 2008). In this study, however, salinity presented very small seasonal variation and thus, it is not expected to influence zooplanktonic assemblages significantly.…”
Section: Zooplanktonmentioning
confidence: 56%
“…Salinity stands out as one of the most important parameters in environments with strong zonation patterns (Gaudy et al, 1995;Marques et al, 2008), or in cases where man-made changes have altered the freshwater inputs in the ecosystem (Sei et al, 1996;Badosa et al, 2008). In this study, however, salinity presented very small seasonal variation and thus, it is not expected to influence zooplanktonic assemblages significantly.…”
Section: Zooplanktonmentioning
confidence: 56%
“…Siphonophores are generally considered strictly oceanic (Pugh, 1999) and intolerant of low salinity waters (Mackie et al, 1987). However, the neritic M. atlantica can exploit both low salinity (Kitamura et al, 2003;Marques et al, 2008;Primo et al, 2012) and high salinity waters (Licandro et al, 2012). Salinity may however have an indirect effect, representing a proxy for physical processes.…”
Section: Discussionmentioning
confidence: 97%
“…Field studies have indicated an upper thermal limit of 24°C for the survival of M. atlantica (Marques et al 2008, Batistić et al 2013. Therefore high tem per ature was unlikely to be a limiting factor in the present study as the maximum average temperature in the Western English Channel is ~16.5 °C (Smyth et al 2010).…”
Section: Discussionmentioning
confidence: 65%